2008
DOI: 10.1016/j.cell.2007.10.057
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Dual Enzyme Ire1 Reveals the Basis for Catalysis and Regulation in Nonconventional RNA Splicing

Abstract: Ire1 is an ancient transmembrane sensor of ER stress with dual protein kinase and ribonuclease activities. In response to ER stress, Ire1 catalyzes the splicing of target mRNAs in a spliceosome-independent manner. We have determined the crystal structure of the dual catalytic region of Ire1at 2.4 A resolution, revealing the fusion of a domain, which we term the KEN domain, to the protein kinase domain. Dimerization of the kinase domain composes a large catalytic surface on the KEN domain which carries out ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
462
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(488 citation statements)
references
References 42 publications
20
462
1
5
Order By: Relevance
“…RTCD1 was previously identified in the HeLa cell extract, and it is an enzyme that catalyzes conversion of a 3 0 -phosphate group into the 2 0 ,3 0 -cyclic phosphodiester at the 3 0 end of RNAs (also named RNA 2,3-cyclic phosphate) in an ATP-dependent manner (23,24). RNA 2,3-cyclic phosphate ends are crucially important in ribosome assembly through regulating RNA-protein binding and RNA stability (27,(29)(30)(31). Previous studies have validated that RTCD1-mediated conversion of 2,3-cyclic phosphate ends on rRNAs is indispensable to 18S rRNA biogenesis (32,33).…”
Section: The Involvement Of Rtcd1 In the Hspc111 Multiprotein Complexmentioning
confidence: 99%
“…RTCD1 was previously identified in the HeLa cell extract, and it is an enzyme that catalyzes conversion of a 3 0 -phosphate group into the 2 0 ,3 0 -cyclic phosphodiester at the 3 0 end of RNAs (also named RNA 2,3-cyclic phosphate) in an ATP-dependent manner (23,24). RNA 2,3-cyclic phosphate ends are crucially important in ribosome assembly through regulating RNA-protein binding and RNA stability (27,(29)(30)(31). Previous studies have validated that RTCD1-mediated conversion of 2,3-cyclic phosphate ends on rRNAs is indispensable to 18S rRNA biogenesis (32,33).…”
Section: The Involvement Of Rtcd1 In the Hspc111 Multiprotein Complexmentioning
confidence: 99%
“…Upon activation, the IRE1 dimer undergoes autotransphosphorylation in which one monomer phosphorylates the other (11). Through the analysis of the structure of the cytosolic domain of IRE1, Lee et al (12) found that dimerization brings together the kinase domains in a face-to-face manner that would seemingly facilitate autotransphosphorylation.…”
mentioning
confidence: 99%
“…Le domaine cytosolique L'oligomérisation du domaine luminal d'IRE1 permet la juxtaposition des domaines cytosoliques et facilite l'autophosphorylation dans le domaine kinase et l'activation du domaine RNase [5]. La structure du domaine cytosolique d'Ire1p (S. cerevisiae) suggère, tout comme celle du domaine luminal, que cette protéine pourrait exister à l'état de dimère en l'absence de stress [5] ( Figure 2 ; partie inférieure du schéma).…”
Section: Ire1 -Généralitésunclassified
“…La structure du domaine cytosolique d'Ire1p (S. cerevisiae) suggère, tout comme celle du domaine luminal, que cette protéine pourrait exister à l'état de dimère en l'absence de stress [5] ( Figure 2 ; partie inférieure du schéma). L'activation pourrait alors résulter de changements conformationnels.…”
Section: Ire1 -Généralitésunclassified
See 1 more Smart Citation